Pengaruh Profitabilitas, Likuiditas, Leverage, dan Ukuran Perusahaan terhadap Kebijakan Dividen - Dicky Hidayat; Sri Hermuningsih; Alfiatul Maulida (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2022)
This study is intended to determine the effect of the independent variable (X), namely: Profitability, Liquidity, Leverage, and Company Size on Dividend Policy in the study of companies in the Consumer Goods Industry sector. The research method in this test uses quantitative descriptive and the data used is secondary data from official sources. The population in this study were all companies in the Consumer Goods Industry sector, totaling 60 companies. The sampling technique in this study was using purposive sampling by taking into account certain conditions that had been agreed upon so that the authors decided to use 10 companies as samples in this test. The data obtained with the observation time of 5 years is 50 data. The source of data in this study is secondary data. Test the quality of the data using Descriptive Analysis Techniques, Classical Assumption Test, and Multiple Linear Analysis. The data analysis technique in this test uses the t statistic test, f statistic test, and the coefficient of determination (Adjust R2). The partial test results in this test show that profitability and liquidity have a positive effect on Dividend Policy, while Leverage and Firm Size have a negative effect on Dividend Policy. Simultaneous test results show that the free factors of Profitability, Liquidity, Leverage, and Company Size also have a positive and significant effect on Dividend Policy in the Consumer Goods Industry sector on the IDX for the 2016-2020 period. Keywords: Profitability, Liquidity, Leverage, Firm Size, Dividend Policy